KEABSAHAN PENGGUNAAN CRYPTOCURRENCY SEBAGAI ALAT TRANSAKSI DI INDONESIA - Prima Rajasa, Ahimsa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The purpose of this study is to examine the legal status of cryptocurrency within the national legal system and to explore its legitimacy as a payment instrument. The development of digital technology has given rise to various innovations in the global payment system, one of which is the emergence of cryptocurrency. Although it is recognized for providing transparency, efficiency, and convenience in financial activities, the position of cryptocurrency as a transactional medium in Indonesia remains a subject of legal controversy. This research employs a normative legal method with both conceptual and statutory approaches, conducted through an analysis of Law Number 7 of 2011 concerning Currency, Bank Indonesia’s financial regulations, and the policies of the Commodity Futures Trading Regulatory Agency (BAPPEBTI). The findings reveal that cryptocurrency is not recognized as a legitimate means of payment, as the prevailing legal framework stipulates that the rupiah is the sole currency with legal tender status for transactions in Indonesia. Nevertheless, the government acknowledges cryptocurrency as a digital asset that may be traded in the futures market. Therefore, using cryptocurrencies for transactions outside from trading digital assets trading may potentially conflict with existing legal provisions. This study emphasizes the need for regulatory reform and integrated supervision to establish a balance between financial technology innovation, legal certainty, and national monetary stability. Keywords: Cryptocurrency, Indonesian Law Financial Regulation